Macroeconomics in retrospect : the selected essays of David Laidler - Laidler, David E. W. (Cheltenham, UK: Edward Elgar Publishing Limited, 2004)
This book brings together nineteen of Laidler's essays on topics in the history of macroeconomics.
Includes bibliographical references and index
gau 17/12/13
Loan
Keywords: Macroeconomics -- History